2016
DOI: 10.1186/s40662-016-0038-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing progression of keratoconus: novel tomographic determinants

Abstract: Several methods have been described in the literature to both evaluate and document progression in keratoconus, but there is no consistent or clear definition of ectasia progression. The authors describe how modern corneal tomography, including both anterior and posterior elevation and pachymetric data can be used to screen for ectatic progression, and how software programs such as the Enhanced Reference Surface and the Belin-Ambrosio Enhanced Ectasia Display (BAD) can be employed to detect earlier changes. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
138
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(163 citation statements)
references
References 52 publications
4
138
0
10
Order By: Relevance
“…The cut-off value we recommend for the D-index is 0.42 to mark a keratoconus eye as progressive, so that further therapeutic steps can be made. D-index is proven to be a reliable parameter in detecting early and definite keratoconus and can highlight changes in the corneal surface earlier than, for example, Kmax 6. It has already been tested as a parameter with which to diagnose keratoconus, but our results indicate that it is suitable to detect disease progression as well since it generated the highest result in our ROC analysis.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The cut-off value we recommend for the D-index is 0.42 to mark a keratoconus eye as progressive, so that further therapeutic steps can be made. D-index is proven to be a reliable parameter in detecting early and definite keratoconus and can highlight changes in the corneal surface earlier than, for example, Kmax 6. It has already been tested as a parameter with which to diagnose keratoconus, but our results indicate that it is suitable to detect disease progression as well since it generated the highest result in our ROC analysis.…”
Section: Discussionmentioning
confidence: 81%
“…Of course, this index has to show the best results, given that progression was defined by the same variables but nevertheless, elevation, steepening and corneal thinning are typical corneal changes when the cornea is affected by keratoconus, and so it makes sense to use these characteristics as well as use them for the definition of progression and detection of progression. Furthermore, previous groups, for example Duncan et al , found the CI for ARC and PRC to be very small in a normative cohort, suggesting that these parameters are suitable for detecting ectatic progression 6. D-index and KPI are a combination of several variables that can all be affected by the disease’s progression, and their meaning and suitability as a marker for progression is emphasised.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard deviation and one-sided confidence intervals for the normal database were previously reported. 56 The keratoconic data were generated by examining three repetitive exams from known keratoconus patients taken on the same day at the University of Auckland, Department of Ophthalmology (Auckland, New Zealand). All patients were fully removed from the Pentacam between exams.…”
Section: Assessing Progression Of Keratoconus and Cross-linking Efficmentioning
confidence: 99%